Human umbilical cord mesenchymal stem cell-derived small extracellular vesicles ameliorate collagen-induced arthritis via immunomodulatory T lymphocytes. (July 2021) - Xu, Ke; Ma, Dan; Zhang, Gailian; Gao, Jinfang; Su, Yazhen; Liu, Sumiao; Liu, Yang; Han, Jian; Tian, Min; Wei, Chun; Zhang, Liyun
Highlights: hUCMSC-sEVs alleviated collagen-induced arthritis. sEVs regulated T lymphocyte proliferation, apoptosis and differentiation into Th17 and Treg cells. sEVs increased the expression of IL-10 and TGF-β, decreased IL-17 expression. Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune disease for which there are currently no effective therapies. Although mesenchymal stem cells (MSCs) can prevent arthritis through immunomodulatory mechanisms, there are several associated risks. Alternatively, MSC-derived small extracellular vesicles (sEVs) can mimic the effects of MSCs, while reducing the risk of adverse events. However, few studies have examined sEVs in the context of RA. Here, we evaluate the immunomodulatory effects of human umbilical cord MSC (hUCMSC)-derived sEVs on T lymphocytes in a collagen-induced arthritis (CIA) rat model to elucidate the possible mechanism of sEVs in RA treatment. We then compare these mechanisms to those of MSCs and methotrexate (MTX). Methods: The arthritis index and synovial pathology were assessed. T lymphocyte proliferation and apoptosis, Th17 and Treg proportions, and interleukin (IL)-17, IL-10, and transforming growth factor (TGF)-β expression were detected using flow cytometry. Retinoic acid receptor-related orphan receptor gamma t (RORγt) and forkhead box P3 (FOXP3), which are master transcriptional regulators of Th17 and Treg differentiation, were also assessed using immunohistochemistry and reverse transcription-polymerase chain reaction (RT-PCR). Results: sEV treatment ameliorated arthritis and inhibited synovial hyperplasia in a dose-dependent manner. These effects were mediated by inhibiting T lymphocyte proliferation and promoting their apoptosis, while decreasing Th17 cell proportion and increasing that of Treg cells in the spleen, resulting in decreased serum IL-17, and enhanced IL-10 and TGF-β expression. Transcriptionally, sEVs decreased RORγt and increased FOXP3 expression in the spleen, and decreased RORγt and FOXP3 expression in the joints. In some aspects sEVs were more effective than MSCs and MTX in treating CIA. Conclusions: hUCMSC-derived sEVs ameliorate CIA via immunomodulatory T lymphocytes, and might serve as a new therapy for RA.